Reduced Threshold for Inhibitory Homeostatic Responses in Migraine Motor Cortex? A tDCS/TMS Study - Cosentino, Giuseppe; Brighina, Filippo; Talamanca, Simona; Paladino, Piera; Vigneri, Simone; Baschi, Roberta; Indovino, Serena; Maccora, Simona; Alfonsi, Enrico; Fierro, Brigida (Headache, 2014)
Background and Objective Neurophysiological studies in migraine have reported conflicting findings of either cortical hyper‐ or hypoexcitability. In migraine with aura (MwA) patients, we recently documented an inhibitory response to suprathreshold, high‐frequency repetitive transcranial magnetic stimulation (hf‐rTMS) trains applied to the primary motor cortex, which is in contrast with the facilitatory response observed in the healthy subjects. The aim of the present study was to support the hypothesis that in migraine, because of a condition of basal increased cortical responsivity, inhibitory homeostatic‐like mechanisms of cortical excitability could be induced by high magnitude stimulation. For this purpose, the hf‐rTMS trains were preconditioned by transcranial direct current stimulation (tDCS), a noninvasive brain stimulation technique able to modulate the cortical excitability state. Methods Twenty‐two MwA patients and 20 patients with migraine without aura (MwoA) underwent trains of 5‐Hz repetitive transcranial magnetic stimulation at an intensity of 130% of the resting motor threshold, both at baseline and after conditioning by 15 minutes of cathodal or anodal tDCS. Motor cortical responses to the hf‐rTMS trains were compared with those of 14 healthy subjects. Results We observed abnormal inhibitory responses to the hf‐rTMS trains given at baseline in both MwA and MwoA patients as compared with the healthy subjects (P < .00001). The main result of the study was that cathodal tDCS, which reduces the cortical excitability level, but not anodal tDCS, which increases it, restored the normal facilitatory response to the hf‐rTMS trains in both MwA and MwoA. Conclusions The present findings strengthen the notion that, in migraine with and without aura, the threshold for inducing inhibitory mechanisms of cortical excitability might be lower in the interictal period. This could represent a protective mechanism counteracting cortical hyperresponsivity. Our results could be helpful to explain some conflicting neurophysiological findings in migraine and to get insight into the mechanisms underlying recurrence of the migraine attacks.